2011
DOI: 10.1557/mrs.2011.205
|View full text |Cite
|
Sign up to set email alerts
|

Starch-based foam composite materials: Processing and bioproducts

Abstract: For the most up-to-date information on 2GCMEA 2012, visit www.mrs.org/2gcmea-2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recently, starch-based expanded foams were developed as environmentally friendly loose-ll packaging materials. 32,33 However, most starch-based foams relied on non-degradable polymers to provide the foam functionality. The PEI-Fc/Em-bCD complex not only has good compressibility, but also "degrades" easily.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, starch-based expanded foams were developed as environmentally friendly loose-ll packaging materials. 32,33 However, most starch-based foams relied on non-degradable polymers to provide the foam functionality. The PEI-Fc/Em-bCD complex not only has good compressibility, but also "degrades" easily.…”
Section: Discussionmentioning
confidence: 99%
“…Starch can be considered as an alternative in the production of foams due to its biodegradability, availability, low cost, abun-dance, and renewability. Starch-based foams are low density materials with many applications including acoustical and/or thermal insulation, packaging and cushioning, [4,31,32] gaskets, and single-use packaging applied as food containers. [4,22,31] Foams are composed of 95-98% gas (water vapor in starch-based foams) as the dispersed phase and the rest is composed of a polymer acting as the continuous phase, building a cellular structure or cell network (open and/or closed cells).…”
Section: Starch-based Foamsmentioning
confidence: 99%
“…70,71 Previous studies [74][75][76] revealed that double helix starch chains were disentangled, rearranged, and entangled together during alkali treatment processing and hence, enhanced the gel viscosity and quality of the starch products. Several nanoparticles [77][78][79][80][81][82][83][84] and layered nanoplatelets [85][86][87][88][89][90][91][92][93] have been reported as potential additives to improve the cellular foaming performance of higher cell density, smaller cell sizes. 78,79,85,87,92 In which, montmorillonite (MMT) nano-platelets are miscible with starch, and can act as efficient nucleation agents for heterogeneous nucleation and microfoaming processing of starch-based polymers even at low MMT loadings.…”
Section: Introductionmentioning
confidence: 99%